Applying Al-Ridha bi al-Syai' Ridha bima Yatawalladu Minhu to Ensure Validity in Islamic Economics - Neni Nuraeni; Muhammad Najib Abdullah (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2023)
The principle al-ridha bi al-Syai' ridha bima yatawalladu minhu, mutual consent to a transaction and its consequences, is pivotal for validating economic exchanges in Islamic finance. This study investigates its role in enhancing accountability, transparency, and ethical integrity within contemporary Islamic economic systems. Using a qualitative descriptive methodology and comprehensive literature review of primary sources (Qur'an, Hadith) and scholarly works, the research analyses how this principle ensures transactional validity by mandating informed consent, risk acceptance, and alignment with maqasid al-shariah (objectives of Islamic law). Key findings reveal that the principle underpins justice in transactions by prohibiting tadlis (deception), requiring full disclosure of risks, and fostering social welfare. Its applications in modern contexts, such as Islamic banking, profit-loss-sharing investments, and fintech (e.g., blockchain, AI), highlight both opportunities and challenges, including regulatory harmonisation and algorithmic transparency. The study concludes that ar-ridha bi-ash-shay'i offers a robust ethical framework adaptable to global economic innovations while upholding core Islamic values. Recommendations include standardised Shariah governance, technology-integrated consent mechanisms, and cross-sector education initiatives.